A Shuttling Protein Kank1 Plays Important Role in the Sex Determination in Yellow Drum - Sun, Sha; Liu, Jieping; Zhang, Sen; He, Qiwei; Han, Wei; Ye, Kun; Han, Fang; Li, Wanbo; Wang, Zhiyong (Frontiers in Marine Science, 2022)
Sex is one of the most important scientific topics, and the existence of sex dimorphism is a conserved feature in vertebrate taxa. The research on sex-determining genes and sex chromosome evolution is a hot topic in biology. The majority of sex-determining genes expressed in somatic cells, and reciprocal interactions between germ cells and somatic cells are important for gonadal differentiation. However, the knowledge of how signals transmission between somatic cells and germ cells remains unclear. In this study, we confirmed the 36 dph was a sex determination critical stage in yellow drum through transcriptome analysis at the early development stages. We further found that Kank1 participated in the germ cells motility process in yellow drum through KEGG pathway analysis together with protein-protein interaction network. With the dual-luciferase reporter assay, we detected that Kank1 increased the transcription of dmrt1_Luc gene in CHO cells and 293T cells. Additionally, we observed that Kank1 was not only expressed in the cytoplasm but also in nucleus in CHO cells through fluorescence microscope. These results suggested that Kank1 acted as a shuttling protein as in human and may play a difunctional role at the early gonad development stage in yellow drum, and it not only participated in the germ cells motility but also increased the expression of dmrt1 in yellow drum.